A method for increasing the use temperature of high-aluminum fiber felt
Through acid leaching and heat treatment methods, the use temperature of high-alumina fiber felt is improved, and the problem of low use temperature of existing high-alumina fiber felt is solved, cost reduction and performance improvement are achieved, and it is suitable for high-temperature applications.
Patent Information
- Application Number
- CN202510088978.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The existing high-aluminum fiber felt has a low operating temperature, resulting in limited application in the high-temperature stage, and the production process consumes huge energy and is too high in cost.
High-alumina fiber felt is prepared by acid leaching, including drying, acid leaching, filtration, water washing, drying and heat treatment, so as to reduce the shrinkage of its heating wire and increase the use temperature.
It increases the use temperature of high-aluminum fiber felt, reduces the preparation cost, enhances the cyclic pressure resistance performance at high temperatures, has low energy consumption, and meets the needs of green development.
Smart Images

Figure CN119507198B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, and in particular to a method for increasing the use temperature of high-aluminum fiber felt. Background Art
[0002] With the development of modern high technology, traditional materials are increasingly difficult to meet the increasingly stringent requirements for material performance in various fields of society. Especially in the fields of turbines, high-temperature sensors, high-temperature kilns, etc., there is an urgent need for new materials that are lightweight, heat-insulating, corrosion-resistant, and have a long life. As a lightweight fibrous refractory material, high-aluminum fiber not only has the characteristics of light weight, high temperature resistance, oxidation resistance, and low thermal stability, but also has the advantages of low thermal conductivity and specific heat capacity, which perfectly meets the performance requirements of materials in the high-temperature field. At present, the alumina content in the high-aluminum fibers produced on the market is generally above 60%. If the alumina content is further increased, the melting temperature will be too high, the fiberization process will be difficult, and the slag ball content will be high. In addition, the production of high-aluminum fibers requires industrial alumina and high-purity silica to be mixed in a certain proportion to form a mass, and then put into a high-temperature arc furnace or resistance furnace for melting. This process consumes a lot of energy, resulting in excessively high production costs for high-aluminum fibers.
[0003] In order to reduce costs, low-purity alumina and silica raw materials are used to prepare high-aluminum fibers with an alumina content of about 70% and an average diameter of less than 1 μm by melt blowing. However, the use temperature of the high-aluminum fiber felt prepared by this method is greatly reduced, and there is an obvious crystallization phenomenon at 900°C. The low use temperature seriously hinders the widespread application of high-aluminum fiber felt in the high-temperature stage. Therefore, an economical and convenient method to increase the use temperature of high-aluminum fiber felt is needed. Summary of the invention
[0004] The present invention provides a method for increasing the use temperature of high-aluminum fiber felt, wherein high-aluminum fiber is treated by an acid leaching method and then prepared into high-aluminum fiber felt, which can reduce the heating line shrinkage of high-aluminum fiber and increase the use temperature of high-aluminum fiber felt. This method can make high-aluminum fiber felt with a lower use temperature also have a higher use temperature, and is an economical and convenient process method.
[0005] In order to achieve the above object, the present invention provides the following scheme:
[0006] A method for increasing the use temperature of high-aluminum fiber felt comprises the following steps:
[0007] S1, drying the high-aluminum fiber;
[0008] S2, acid leaching treatment, immersing the dried high-aluminum fiber in an acid leaching solution, and placing it in a constant temperature water bath for heat preservation treatment to obtain the high-aluminum fiber after acid leaching treatment, the set temperature of the constant temperature water bath is 30-100°C, and the constant temperature insulation time is 2-10h; the ratio of the acid leaching solution to the high-aluminum fiber is 20-50g of high-aluminum fiber per liter of the acid leaching solution; this step is to allow the high-aluminum fiber to fully contact the acid leaching solution and fully react with the acid leaching solution; the concentration of nitric acid in the acid leaching solution is 0.1-2mol / L, and the concentration of aluminum nitrate is 10%-100% saturated;
[0009] S3, filtering treatment, filtering the high-aluminum fiber after acid leaching to remove the acid leaching liquid and unreacted chemical substances on the fiber surface. Then the high-aluminum fiber is washed with water for multiple times to obtain the washed high-aluminum fiber;
[0010] S4, drying treatment, drying the cleaned high-aluminum fiber, and cooling it to room temperature to obtain the dried high-aluminum fiber;
[0011] S5, dispersing and filtering the dried high-aluminum fibers into felt;
[0012] S6. Perform heat treatment at 900°C for 2h to obtain high-aluminum fiber felt.
[0013] Furthermore, the concentration of nitric acid in the acid leaching solution is 0.1 to 1 mol / L. The concentration of aluminum nitrate is 50% to 100% saturated. The high-aluminum fiber is acid-leached using a nitric acid solution, and a certain amount of aluminum nitrate is added to the nitric acid solution to inhibit the dissolution of aluminum oxide in the high-aluminum fiber.
[0014] Furthermore, the acid leaching solution is prepared by adding concentrated nitric acid and aluminum nitrate nonahydrate powder into water, stirring until the powder is completely dissolved to obtain the acid leaching solution;
[0015] Furthermore, the ratio of the acid leaching solution to the high-aluminum fiber is 30 to 40 g of high-aluminum fiber per liter of the acid leaching solution.
[0016] Furthermore, the drying process in S1 is specifically to place the high-aluminum fiber in a constant temperature drying oven for drying at a temperature of 90-100° C. for a drying time of 20-26 hours. This process is intended to remove moisture from the high-aluminum fiber so that the high-aluminum fiber can be subsequently chemically treated.
[0017] Furthermore, the set temperature of the constant temperature water bath in S2 is 30-70° C., and the constant temperature insulation time is 2-7 hours.
[0018] Furthermore, the drying in S4 specifically includes: placing the cleaned high-aluminum fiber into a crucible and drying it in a constant temperature drying oven to remove excess moisture. The temperature of the constant temperature drying oven is 110-120° C., and the drying time is 10-16 hours.
[0019] The method of the present invention is to prepare high-aluminum fiber felt by acid leaching high-aluminum fiber with low use temperature prepared from low-purity raw materials, dispersing, filtering and pressing to form felt, and then heat treating at 900°C. The prepared high-aluminum fiber felt has reduced heating line shrinkage and increased use temperature. This is because the acid leaching solution contains nitric acid and aluminum nitrate. When the high-aluminum fiber reacts with the acid leaching solution, impurities such as iron oxide in the high-aluminum fiber can be dissolved, aluminum salts are introduced, and Al 3+ The concentration is reduced, the dissolution of alumina is suppressed, and the content of impurities such as iron oxide in the high-alumina fiber after acid leaching is significantly reduced, thereby improving the purity of the high-alumina fiber. The heating line shrinkage of the high-alumina fiber felt is further reduced by heat treatment at 900°C, and the use temperature is greatly improved.
[0020] The advantages and beneficial effects of the present invention are:
[0021] 1. The method of the present invention can greatly reduce the shrinkage of the heating line of the high-aluminum fiber felt with a low operating temperature, increase the operating temperature, and reduce the preparation cost of the high-aluminum fiber.
[0022] 2. The method of the present invention can enhance the cyclic pressure resistance of high-aluminum fiber felt above 1300°C, and can withstand greater stress of 140 to 200 kPa. After heat treatment at 1400°C, the stress is 590 to 860 kPa.
[0023] 3. The method of the present invention has low processing temperature and low energy consumption, which meets the needs of green development. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a process flow chart of the method of the present invention.
[0025] Figure 2 This is a microscope picture of the high-aluminum fiber after treatment in Example 1;
[0026] Figure 3 This is a microscope picture of the high-aluminum fiber after treatment in Example 2;
[0027] Figure 4 This is a microscope picture of the high-aluminum fiber after treatment in Example 3;
[0028] Figure 5 The SEM images of the high aluminum fibers after being treated in Example 1, Example 3, Comparative Example 2 and Comparative Example 3, wherein (a) corresponds to Example 1, (b) corresponds to Example 3, (c) corresponds to Comparative Example 2, and (d) corresponds to Comparative Example 3;
[0029] Figure 6 This is a microscope picture of the high-aluminum fiber after treatment in Comparative Example 2;
[0030] Figure 7This is a microscope picture of the high-aluminum fiber after treatment in Comparative Example 3;
[0031] Figure 8 Length variation diagram of the high-aluminum fiber felt prepared in Example 1 and the original high-aluminum fiber felt before and after treatment at different temperatures;
[0032] Fig. 9 Example 1: Heating line variation diagram of high-aluminum fiber filter press felt after acid washing and original high-aluminum fiber felt treated at different temperatures;
[0033] Fig.10 It is a curve diagram of the heating line of the original high-aluminum fiber felt, the high-aluminum fiber felt prepared in Example 2 and the comparative example 1 as the temperature changes;
[0034] Fig.11 The high aluminum fiber felt prepared in Example 1 and the original high aluminum fiber felt were subjected to pressure resistance test at 1300°C; (a) is the original high aluminum fiber felt, and (b) is the high aluminum fiber felt prepared in Example 1;
[0035] Fig.12 The high-aluminum fiber felt prepared in Example 1 and the original high-aluminum fiber felt were subjected to pressure resistance test at 1400°C. (a) is the original high-aluminum fiber felt, and (b) is the high-aluminum fiber felt prepared in Example 1. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0037] Example 1
[0038] A method for increasing the use temperature of high-aluminum fiber felt comprises the following steps:
[0039] S1. Drying the high-aluminum fiber; drying the high-aluminum fiber obtained by the blowing method in a constant temperature drying oven; wherein the temperature of the constant temperature drying oven is 90° C., and the drying time is 24 hours.
[0040] S2, acid leaching treatment: prepare an acid leaching solution, add aluminum nitrate nine hydrate powder to the nitric acid solution, and mix thoroughly until the aluminum nitrate nine hydrate is completely dissolved; wherein, the concentration of nitric acid in the acid leaching solution is 0.10 mol / L, and the concentration of aluminum nitrate is 50% saturated. Among them, the method to ensure that the concentration of nitric acid and aluminum nitrate meet the requirements is to determine the required volume of the acid leaching solution according to the mass of the high-aluminum fiber to be treated, and then calculate the required molar mass of concentrated nitric acid and aluminum nitrate nine hydrate according to the concentration of nitric acid and aluminum nitrate in the optimal acid leaching solution, and then obtain the corresponding volume and mass. First, use a small amount of deionized water to fully mix and stir the required concentrated nitric acid and aluminum nitrate nine hydrate. After the powder is fully dissolved, add deionized water to the solution until the solution volume is 250 mL, and finally use a 250 mL volumetric flask to titrate and configure the final optimal acid leaching solution.
[0041] The high-aluminum fiber was immersed in the acid leaching solution and then placed in a constant temperature water bath for heat preservation; in order to ensure that the high-aluminum fiber and the acid leaching solution fully reacted, the ratio of the acid leaching solution to the high-aluminum fiber was 250 ml: 8 g. The temperature of the constant temperature water bath was set at 30°C and the water bath heat preservation time was 3 hours.
[0042] S3, filtering, filtering the high-aluminum fiber after acid leaching by suction filtration through a Buchner funnel and washing it multiple times with deionized water to obtain washed high-aluminum fiber;
[0043] S4, drying treatment, the cleaned high-aluminum fiber is placed in a crucible and then dried in a constant temperature drying oven to remove excess water, thereby obtaining the dried high-aluminum fiber. The drying temperature of the constant temperature drying oven is 120° C., and the drying time is 12 hours.
[0044] S5, dispersing and filtering the high-aluminum fibers dried in S4 into felt;
[0045] S6. Perform heat treatment at 900°C for 2h to obtain high-aluminum fiber felt.
[0046] The microscope image of the high aluminum fiber after treatment in Example 1 is as follows: Figure 2 As shown in the SEM images Figure 5 As shown in Figure (a), there is almost no trace of acid corrosion on the surface of the high-aluminum fiber; the contents of the main substances in the high-aluminum fiber are shown in Table 1. The high-aluminum fiber felt was heat-treated and the length change during the heat treatment was measured. Figure 8 After 1300℃ and 1400℃, the pressure resistance test is carried out. Fig.11 Middle (b), Fig.12 As shown in (b).
[0047] Example 2
[0048] The difference from Example 1 is that the concentration of nitric acid in the acid leaching solution is 0.5 mol / L, and the concentration of aluminum nitrate is 50% saturated.
[0049] The microscope image of the high aluminum fiber after treatment in Example 2 is as follows: Figure 3 As shown, the microstructure of the high aluminum fiber has not changed significantly; the contents of the main components in the high aluminum fiber are shown in Table 1.
[0050] Example 3
[0051] A method for increasing the use temperature of high-aluminum fiber felt comprises the following steps:
[0052] S1. Drying the high-aluminum fiber; drying the high-aluminum fiber obtained by the blowing method in a constant temperature drying oven; wherein the temperature of the constant temperature drying oven is 90° C., and the drying time is 24 hours.
[0053] S2, acid leaching treatment, adding aluminum nitrate nonahydrate powder to the nitric acid solution, and mixing thoroughly until the aluminum nitrate nonahydrate is completely dissolved; the preparation method is the same as that of Example 1, wherein the concentration of nitric acid in the acid leaching solution is 1.00 mol / L, and the concentration of aluminum nitrate is 100% saturated.
[0054] The high-aluminum fiber was immersed in the acid leaching solution and then placed in a constant temperature water bath for heat preservation; in order to ensure that the high-aluminum fiber and the acid leaching solution fully reacted, the ratio of the acid leaching solution to the high-aluminum fiber was 250 ml: 8 g. The constant temperature water bath was set at 70°C and the water bath heat preservation time was 7 hours.
[0055] S3, filtering by suction, filtering the high-aluminum fiber after acid leaching by a Buchner funnel and washing it with deionized water for multiple times to obtain washed high-aluminum fiber;
[0056] S4, drying, the cleaned high-aluminum fiber is placed in a crucible and then dried in a constant temperature drying oven to remove excess water, thereby obtaining dried high-aluminum fiber. The drying temperature of the constant temperature drying oven is 100° C., and the drying time is 12 hours.
[0057] S5, dispersing and filtering the high-aluminum fibers dried in S4 into felt;
[0058] S6. Perform heat treatment at 900°C for 2h to obtain high-aluminum fiber felt.
[0059] The microscope image of the high aluminum fiber after treatment in Example 3 is as follows: Figure 4 As shown in the SEM images Figure 5 As shown in Figure (b), the microstructure of the high-aluminum fiber has not changed significantly. Although there are traces of erosion, the degree of erosion is low and there are no deep dents on the surface. The contents of the main components in the high-aluminum fiber are shown in Table 1.
[0060] Comparative Example 1
[0061] A method for increasing the use temperature of a high-aluminum fiber felt, which is different from Example 2 in that the high-aluminum fiber felt is directly prepared using original high-aluminum fibers, and then the high-aluminum fiber felt is subjected to acid leaching, comprising the following steps:
[0062] S1, drying, dispersing and filter pressing the original high-aluminum fiber to prepare high-aluminum fiber felt;
[0063] S2. Pretreatment: Put the high-aluminum fiber felt into a high-temperature resistance furnace for pretreatment. The temperature of the resistance furnace is set to 900° C. and the insulation time is 2 hours.
[0064] S3, acid leaching treatment. The method for preparing the acid leaching solution is the same as that in Example 2, except that the concentration of nitric acid in the acid leaching solution is 0.1 mol / L, and the concentration of aluminum nitrate is 50% saturated.
[0065] Add high-aluminum fiber felt into the acid leaching solution and then put it into a constant temperature water bath for heat preservation; in order to ensure that the high-aluminum fiber felt and the acid leaching solution fully react, the ratio of the acid leaching solution to the high-aluminum fiber felt is 250ml:8g. The water bath temperature is set at 30℃ and the water bath insulation time is 3h.
[0066] S5, filtering, filtering the high-aluminum fiber felt and washing it multiple times with deionized water to obtain a washed high-aluminum fiber felt;
[0067] S6, drying, the filtered high-aluminum fiber felt is placed in a crucible and then dried in a constant temperature drying oven to remove excess water, thereby obtaining the acid-leached high-aluminum fiber felt. The drying temperature of the constant temperature drying oven is 120° C., and the drying time is 12 hours.
[0068] The contents of the main components in the high-aluminum fiber felt after treatment in Comparative Example 1 are shown in Table 1.
[0069] Comparative Example 2
[0070] The only difference from Example 1 is that the concentration of nitric acid in the acid leaching solution is 2.5 mol / L.
[0071] The SEM image of the high aluminum fiber after treatment in Comparative Example 2 is as follows: Figure 5 The microscope image is shown in (c). Figure 6 As shown in Table 1, the microstructure of high-aluminum fiber is seriously corroded by acid, and the fiber surface has been delaminated due to acid corrosion. The contents of the main components in high-aluminum fiber are shown in Table 1.
[0072] Comparative Example 3
[0073] The only difference from Example 1 is that the concentration of nitric acid in the acid leaching solution is 2 mol / L.
[0074] The SEM image of the high aluminum fiber after treatment in Comparative Example 3 is as follows: Figure 5 As shown in (d). Microscope images are shown in Figure 7 As shown in Table 1, the traces of acid corrosion can be clearly seen on the surface of high-aluminum fiber. The contents of the main components in high-aluminum fiber are shown in Table 1.
[0075] Comparative Example 4
[0076] The only difference from Example 1 is that during the acid leaching treatment, the temperature of the constant temperature water bath is set to 25°C.
[0077] The contents of the main components in the high-aluminum fiber after treatment in Comparative Example 4 are shown in Table 1.
[0078] Comparative Example 5
[0079] The only difference from Example 1 is that during the acid leaching treatment, the temperature of the constant temperature water bath is set to 105°C.
[0080] The contents of the main components in the high-aluminum fiber after treatment in Comparative Example 5 are shown in Table 1.
[0081] Comparative Example 6
[0082] The only difference from Example 1 is that no aluminum nitrate is added during the acid leaching treatment.
[0083] The contents of the main components in the high-aluminum fiber after treatment in Comparative Example 6 are shown in Table 1.
[0084] Comparative Example 7
[0085] The difference from Example 1 is that the high-aluminum fiber is not acid-washed but alkali-washed, and the dried high-aluminum fiber is added with NaOH solution, the ratio of high-aluminum fiber to NaOH solution is 8g:250mL, and magnetic stirring is performed at room temperature for 2h. The alkali-washed high-aluminum fiber is then filtered to remove excess alkali, and finally placed in a 90°C oven for drying and taken out.
[0086] The main components of high-aluminum fiber after alkali washing are shown in Table 1. The alkali washing process cannot change the chemical composition of the fiber.
[0087] Table 1 Main component contents of high aluminum fiber before acid leaching and after treatment in Examples and Comparative Examples
[0088]
[0089] It can be seen from Table 1 that the sum of the contents of alumina and silica in the high-alumina fibers after treatment in Examples 1 to 3 is relatively increased, while the contents of iron oxide and calcium oxide are decreased; in Comparative Example 1, after the fiber felt is first prepared and then pickled, the sum of the contents of alumina and silica in the high-alumina fibers is slightly increased, and the decrease in the contents of iron oxide and calcium oxide is not as obvious as in the examples; in Comparative Examples 2 and 3, the concentration of nitric acid is changed, the content of alumina is significantly decreased, and the sum of the contents of alumina and silica is relatively decreased, while the contents of iron oxide and calcium oxide are not as significantly decreased as in the examples, indicating that as the concentration of nitric acid increases, the acid corrosion of the fiber is more serious, causing damage to the fiber structure, resulting in a relative decrease in the sum of the contents of alumina and silica.
[0090] In Comparative Examples 4 and 5, the acid immersion temperature is set to 25°C and 105°C, respectively. It can be seen that in the high-aluminum fiber after treatment, the sum of the contents of aluminum oxide and silicon dioxide does not change significantly, but the content of iron oxide is increased compared to Example 1, which indicates that a reaction temperature that is too low or too high is not conducive to reducing the iron oxide content in the high-aluminum fiber.
[0091] In Comparative Example 6, aluminum nitrate is not added. The aluminum oxide content in the high-aluminum fiber after acid leaching is greatly reduced, and the iron oxide content is also increased compared with Example 1. This shows that the addition of aluminum nitrate can effectively reduce the dissolution of aluminum oxide in the high-aluminum fiber, increase the dissolution ratio of iron oxide, and thereby reduce the iron oxide content in the high-aluminum fiber.
[0092] The high-aluminum fiber felt prepared in Example 1 and the original high-aluminum fiber felt were cut into rectangular samples of 20 mm × 20 mm × 60 mm, placed in a box furnace and heated to 1000°C, 1100°C, 1200°C, 1300°C, and 1400°C in sequence, and taken out after keeping warm for 24 hours. The length change data before and after heat treatment were measured, and the data were plotted into images to obtain Figure 8 It can be seen that when the heat treatment temperature exceeds 1300℃, the length change of the high-aluminum fiber after pickling is significantly reduced compared with the high-aluminum fiber without pickling, indicating that the performance of the high-aluminum fiber after pickling is relatively stable in the high temperature stage.
[0093] The length of the 20mm×20mm×60mm fiber felt at each initial temperature is taken as the reference, and then the length of the fiber after burning at each temperature is divided by the reference, and the line change plot of the high-aluminum fiber felt is obtained. Fig. 9 In Example 1, after the filter press felt is not subjected to heat treatment, the linear shrinkage of the original high-aluminum fiber felt is smaller, and the maximum operating temperature can be maintained at 1100°C. Fig. 9As shown in (a); if the fiber felt after 800°C heat treatment after filter pressing in Example 1 is used as the original sample for calculation, the fiber felt prepared from the acid-washed fiber has no obvious shrinkage in the range of 1000-1200°C. When the temperature is not higher than 1200°C, the shrinkage rate of the high-aluminum fiber felt prepared from the acid-washed fiber is greater than that of the original high-aluminum fiber felt, such as Fig. 9 As shown in (b); if the fiber prepared in Example 1 is the original sample for calculation, the linear shrinkage of the original high-aluminum fiber felt after heat treatment at 900°C is greater than that of the high-aluminum fiber felt prepared in Example 1, and the shrinkage of the two fiber felts at 1200°C is less than 4%. As the temperature rises to 1300°C, the shrinkage of the high-aluminum fiber felt prepared in Example 1 is still less than 4%, and the shrinkage of the original high-aluminum fiber felt after heat treatment at 900°C is much greater than 40%, as shown in FIG. Fig. 9 As shown in (c), the linear change data of the high-aluminum fiber felt prepared in Example 1 is compared with the original high-aluminum fiber felt after heat treatment at 900°C. It can be seen that the linear shrinkage of the high-aluminum fiber felt prepared in Example 1 above 1200°C is significantly lower than that of the original high-aluminum fiber felt. Fig. 9 It can be seen that the high-aluminum fiber felts all show a shrinkage trend after being heat-treated at 900°C. The linear change of the high-aluminum fiber felt does not increase significantly with the increase of temperature; when the temperature rises to above 1200°C, the linear change of the high-aluminum fiber felt increases with the increase of temperature. At this time, the linear shrinkage of the high-aluminum fiber felt prepared in Example 1 is significantly lower than that of the original high-aluminum fiber felt. It can be confirmed that acid immersion treatment and heat treatment at 900°C can effectively reduce the heating linear shrinkage of fiber felts above 1200°C, so that its use temperature reaches above 1300°C. This is because after pickling, the content of impurities such as iron oxide and calcium oxide in the high-aluminum fiber is reduced, resulting in a significant reduction in the linear shrinkage of the high-aluminum fiber at high temperatures.
[0094] The curves of the heating wires of the original high-aluminum fiber felt, Example 2 and Comparative Example 1 as the temperature changes are as follows: Fig.10 As shown, it can be seen that when the temperature exceeds 1200°C, the heating line shrinkage of the high-aluminum fiber felt prepared in Example 2 is significantly reduced. In Comparative Example 1, the high-aluminum fiber felt is first prepared and then pickled. Compared with the original high-aluminum fiber felt, the heating line shrinkage is reduced, but compared with Example 2, the high-aluminum fiber is first pickled and then prepared. The heating line shrinkage is still very high. Therefore, the process of pickling first and then preparing the high-aluminum fiber felt is more conducive to reducing the heating line shrinkage of the original high-aluminum fiber and increasing the use temperature of the high-aluminum fiber.
[0095] The high-aluminum fiber felt prepared in Example 1 and the original high-aluminum fiber felt were subjected to a pressure resistance test after heat treatment at 1300°C and 1400°C. The fiber felt was cut into 20mm×20mm×20mm blocks, with a height equal to the thickness of the high-aluminum fiber felt. A universal testing machine was used, with each pressurization displacement set to 20% of the thickness of the high-aluminum fiber felt block. The pressure was cycled 10 times to obtain the stress-deformation relationship data of the high-aluminum fiber felt block. Fig.11 , Fig.12 As shown in the figure, the high-aluminum fiber felt after pickling can withstand greater stress and also has a certain degree of resilience, and the overall performance of use will be better. The reason for this result is that the pickling treatment causes some fiber filaments in the original high-aluminum fiber to be corroded, and the average fiber filament length is shorter. After being made into a high-aluminum fiber felt sample, the high-aluminum fiber felt has a higher density and smaller pores, so it can withstand greater stress.
[0096] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.
Claims
1. A method for increasing the use temperature of high-aluminum fiber felt, characterized in that: The following steps are involved: S1. Drying the high-aluminum fiber; S2, acid leaching treatment, immersing the dried high-aluminum fiber in an acid leaching solution, and placing it in a constant temperature water bath for heat preservation treatment to obtain the high-aluminum fiber after acid leaching treatment, the set temperature of the constant temperature water bath is 30-100°C, and the constant temperature insulation time is 2-10h; the ratio of the acid leaching solution to the high-aluminum fiber is 20-50g of high-aluminum fiber per liter of the acid leaching solution; the concentration of nitric acid in the acid leaching solution is 0.1-2 mol / L, and the concentration of aluminum nitrate is 10%-100% saturated; S3, filtering treatment, filtering the high-aluminum fiber after acid leaching treatment, and then washing the high-aluminum fiber with water for multiple times to obtain washed high-aluminum fiber; S4, drying treatment, drying the cleaned high-aluminum fiber, and cooling it to room temperature to obtain the dried high-aluminum fiber; S5, dispersing and filtering the dried high-aluminum fibers into felt; S6. Perform heat treatment at 900°C for 2h to obtain high-aluminum fiber felt.
2. The method according to claim 1, characterized in that The concentration of nitric acid in the acid leaching solution is 0.1-1 mol / L, and the concentration of aluminum nitrate is 50%-100% saturated.
3. The method according to claim 1, characterized in that The preparation method of the acid leaching solution is as follows: adding concentrated nitric acid and aluminum nitrate nonahydrate powder into water, and stirring until the powder is completely dissolved to obtain the acid leaching solution.
4. The method according to claim 1, characterized in that: The ratio of the acid leaching solution to the high-aluminum fiber is 30-40 g of high-aluminum fiber per liter of the acid leaching solution.
5. The method according to claim 1, characterized in that The drying process in S1 is specifically to place the high-aluminum fiber in a constant temperature drying oven for drying at a temperature of 90-100° C. for a drying time of 20-26 hours.
6. The method according to claim 1, characterized in that The set temperature of the constant temperature water bath in S2 is 30-70° C., and the constant temperature insulation time is 2-7 hours.
7. The method according to claim 1, characterized in that The drying in S4 is specifically as follows: the cleaned high-aluminum fiber is placed in a crucible and then dried in a constant temperature drying oven, the temperature of the constant temperature drying oven is 110-120° C., and the drying time is 10-16 hours.
Citation Information
Patent Citations
Chemical strengthening method of medium-high aluminum silicate glass fiber
CN113800786A
Preparation method of 1500 type refractory fiber blanket and refractory fiber module
CN118292187A